2021
DOI: 10.1177/15563316211039203
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Arthroplasty in Patients With Prior Ipsilateral Hip Fusion: A Surgical Technique

Abstract: Background: In patients with severe osteoarthritis of the knee with prior ipsilateral hip fusion who require total knee arthroplasty (TKA), a controversial issue is whether to first convert the hip fusion to a total hip arthroplasty (THA) or to perform TKA without reconstruction of the hip. Also, immobility of the ipsilateral, fused hip adds significant technical challenge because the usual positioning of the leg requires modification in order to gain access needed for the TKA. Technique: In such cases, we pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Samborski et al [22] used multiple mattresses to raise the upper part of the body, the knee being positioned on the surgical table in the Mayo support that offered the possibility of controlled flexion. Ullan et al [23] positioned the limb in the Postoperative X-rays revealed adequate positioning and sizing of the prosthetic components and a restored alignment of the lower limb. Personalized rehabilitation was initiated 24 h after the surgery, with knee flexion being recovered at the edge of the bed, and knee extension in lateral decubitus; weight bearing was allowed on the 1st postoperative day, and the patient started walking with the aid of crutches.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Samborski et al [22] used multiple mattresses to raise the upper part of the body, the knee being positioned on the surgical table in the Mayo support that offered the possibility of controlled flexion. Ullan et al [23] positioned the limb in the Postoperative X-rays revealed adequate positioning and sizing of the prosthetic components and a restored alignment of the lower limb. Personalized rehabilitation was initiated 24 h after the surgery, with knee flexion being recovered at the edge of the bed, and knee extension in lateral decubitus; weight bearing was allowed on the 1st postoperative day, and the patient started walking with the aid of crutches.…”
Section: Resultsmentioning
confidence: 99%
“…Searching the PubMed and Google Scholar databases for "total knee arthroplasty" and "ipsilateral hip fusion/arthrodesis/ankylosis", we found 81 articles, out of which 12 included our criteria: patients with hip fusion/ankylosis/arthrodesis and ipsilateral knee osteoarthritis treated with a total knee replacement. These 12 studies followed and described the total knee arthroplasty in a total of 30 patients with ipsilateral hip fusion (Table 1) [1,3,9,[16][17][18][19][20][21][22][23][24]. Callaghan et al [1] was the first to mention the possibility of performing a TKA in a patient with same side hip fusion, without giving too many details about the respective patients or surgical technique.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations